2022
DOI: 10.1007/s00431-022-04486-9
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and quality of life in parents of children with congenital hyperinsulinism

Abstract: This study aimed to assess mental health, family burden, and quality of life (PQoL) in parents of children with persistent congenital hyperinsulinism (CHI). Forty-eight individual CHI parents (75% female) completed self-reported questionnaires and screening tools for anxiety (GAD-7), depression (PHQ-8), PQoL (ULQIE), and family burden (FaBeL). Additional data on sociodemographics, social support, and child- and disease-related data were recorded. 29.8% of parents showed major depressive symptoms and 38.3% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…One of the main characteristics of mental health and wellbeing, as highlighted by the WHO (WHO, 2021 ), is establishing positive relationships that help individuals face challenges. Indeed, there is a whole body of research on the link between having quality relationships and strong support networks and several positive health outcomes (Huang et al, 2017 ; Roeper et al, 2022 ). The present study shows that the DLG conducted in a primary health care centre impacted on the creation of solidarity and friendship relationships among participants, which helped many of them break the feeling of loneliness and overcome hardships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main characteristics of mental health and wellbeing, as highlighted by the WHO (WHO, 2021 ), is establishing positive relationships that help individuals face challenges. Indeed, there is a whole body of research on the link between having quality relationships and strong support networks and several positive health outcomes (Huang et al, 2017 ; Roeper et al, 2022 ). The present study shows that the DLG conducted in a primary health care centre impacted on the creation of solidarity and friendship relationships among participants, which helped many of them break the feeling of loneliness and overcome hardships.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a wealth of scientific literature on the impact of strong social relationships and friendships on wellbeing and health, both physical and mental (Bosle et al, 2022 ; Gan & Best, 2021 ; Glaser et al, 2023 ). Having strong support networks is related with a lower prevalence of illnesses, such as cardiometabolic risk (Shartle et al, 2022 ); better health behaviours (Li & Yan, 2020 ); and improved mental health outcomes (Roeper et al, 2022 ), such as preventing suicidal ideation (Huang et al, 2017 ). For instance, several studies have shown that feelings of social connectedness and a sense of community were key for mitigating the impacts of COVID-19 and the lockdowns on wellbeing (Humphrey et al, 2022 ; Mannarini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings open the door for the development of neuroimaging biomarkers to assess neurological involvement and response to investigational therapies in HI [40 ▪ ]. Roeper et al performed the first systematic evaluation of psychosocial well-being for caregivers of children with HI [41]. The authors found high rates of caregiver anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%